The Meaning of Japanese Proverbs and Their Equivalents in Indonesian Language - Aulia, Muhamad Faza; Tresnasari, Ningrum (Universitas Diponegoro, 2022)
Proverbs in Japanese are known as Kotowaza, which are defined as wise sayings or ancient proverbs that have many practical benefits. This study aims to examine the understanding of Japanese language students in Bandung city regarding the meaning of proverbs and their equivalents in Indonesian. The research method used is descriptive quantitative with the theory used for analysis is Ogden and Richard's triangle of meaning theory. This paper is expected to be an insight in understanding the meaning of proverbs. Although each word in these proverbs has a different meaning, when formed into a proverb in both Indonesian and Japanese, it will give rise to a new meaning that contains sarcasm, advice or simply reinforces the meaning of each utterance. The word elements used to form proverbs in Japanese and Indonesian are the same, but the meaning will be different depending on the culture of the people. The results of the analysis showed that out of 41 students of Japanese language study programs in Bandung, 29 students understood the meaning of some of the Japanese proverbs given, although the proverbs were not learned in their formal education. As for the Indonesian equivalents, each of these Japanese proverbs has two Indonesian equivalents. <a href=